2019
DOI: 10.1039/c9cp02474c
|View full text |Cite
|
Sign up to set email alerts
|

Stable, one-dimensional suspended and supported monatomic chains of pnictogens: a metal–insulator framework

Abstract: Group-VA elements P, As, Sb, and Bi can construct free-standing, stable zigzag monatomic chain structures, which show unusual properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Furthermore, it has been pointed out that the confined phosphorus and arsenic materials could be used for making P 4 and As 4 , respectively, available for chemical reactions. ,,, Whether longer chain segments can be recovered intact from inside the SWCNTs using appropriate solvents is another open question. A recent computational study has suggested that the one-dimensional pnictogen zigzag chains may be stable when supported by a substrate . Finally, as we have shown here, moving toward larger-diameter SWCNTs opens a door to ever more complex pnictogen materials.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, it has been pointed out that the confined phosphorus and arsenic materials could be used for making P 4 and As 4 , respectively, available for chemical reactions. ,,, Whether longer chain segments can be recovered intact from inside the SWCNTs using appropriate solvents is another open question. A recent computational study has suggested that the one-dimensional pnictogen zigzag chains may be stable when supported by a substrate . Finally, as we have shown here, moving toward larger-diameter SWCNTs opens a door to ever more complex pnictogen materials.…”
Section: Discussionsupporting
confidence: 64%
“…A recent computational study has suggested that the one-dimensional pnictogen zig-zag chains may be stable when supported by a substrate. 75 Finally, as we have shown here, moving towards larger diameter SWCNTs opens a door to ever more complex pnictogen materials. Exploring their structures and physical properties in detail will be an exciting future challenge.…”
Section: Computational Energies and Bandgaps Of The One-dimensional Pmentioning
confidence: 56%
“…Several studies have demonstrated the advantage of a 3D-printed fracture model over CT imaging alone for the diagnosis of complex fractures [ 40 , 41 ]. This study showed, that the implementation of point of care 3D-printing may provide additional value when compared to the sole use of conventional imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical calculation first predicted the existence of true 1D phosphorene atomic chains [28]. In spite that the fabrication of the narrowest nanostructures of BP from 2D materials can be quite a challenge, there are several experiments that have successfully grown 1D atomic chains using various advanced techniques [29][30][31].…”
Section: Introductionmentioning
confidence: 99%